Intelligent Flood Dispatching in River Basins Based on Knowledge Graphs - SONG Wanli; XIONG Xian; YANG Haihua; ZHU Sha; FENG Yuwei; WANG Zhaoli (Renmin Zhujiang)
Aimed at regulating the water level during flood seasons, controlling the discharge and ensuring the power generation output, flood dispatching of cascade hydropower stations plays an important role in alleviating the flood control pressure in the lower reaches of the basins and protecting the life safety of residents. However, the information retrieval efficiency of traditional flood dispatching systems is low, and it is difficult to satisfy the requirement of unified management, centralized dispatching, and close coordination. To this end, this paper introduces the basic theory and technical methods of knowledge graphs. Meanwhile, by taking the cascade hydropower station in the Beipanjiang River Basin as an example, it analyzes the data such as basic performance parameters and dispatching procedures of the reservoir. Regular expression matching and the TF-IDF method are adopted to complete flood dispatching knowledge extraction and integration, and thus construct a flood dispatching rule library and scheme set. Additionally, a top-down approach is employed to build a knowledge graph for flood dispatching in the basin, facilitate information retrieval, and enable intelligent early warning and automatic scheme push for floods, thereby providing references for the construction of intelligent flood dispatching systems in basins.